The Influence of Financial Literacy, Lifestyle on Financial Management Behavior with Self Control as an Intervening Variable Study on the Student Exchange Program at Mataram University - Yustina, Eka Putri; Lestari, Baiq Anggun Hilendri (PT FORMOSA CENDEKIA GLOBAL, 2024)
Indonesia entered an era of revolution that continued to develop with this flight, students are required to adapt to existing development patterns such as social media platforms or e-commerce with financial literacy, lifestyle, and self-control as the basis for managing student finances. This research aims to determine the impact that financial literacy, lifestyle, and self-control have on the financial management of the student exchange program at Mataram University. This research uses quantitative methods with a descriptive quantitative type. The population in this study were the student exchange at Mataram University, using the purposive sampling method with the Slovin technique so that the total sample obtained was 150 students. The research results showed a significant effect but lifestyle had an insignificant impact. After going through the second model, namely intervening, it was found that all the results had a significant effect through self-control as an intermediate variable.